Peran motivasi instrinsik, pemberdayaan, komitmen dan konflik pada peningkatan kinerja karyawan Koperasi - Guridno, Eddy; Sismati, Zahra Meike (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
Studies regarding factors that can improve employee performance will continue to be studied. Therefore, this research aims to examine the influence of motivation, commitment, empowerment and conflict on the performance of cooperative employees. The research population is employees who are members of the Permata Bank Bintaro Cooperative cooperative in Tangerang. A total of 105 employees were respondents with a saturated sample, the total sample who returned the questionnaire was 103 respondents. Hypothesis testing analysis by carrying out multiple regression tests using SPSS 24. The results of multiple regression testing with SPSS 24 show that all independent variables, namely motivation, commitment, empowerment and conflict, positively influence employee performance. Therefore, it is recommended that cooperatives continue to improve the performance of their employees by increasing the intrinsic motivation and organizational commitment of their employees. Likewise, it is necessary to support a culture of employee empowerment and appropriate conflict handling.